15m-2(3+5m)=

Simple and best practice solution for 15m-2(3+5m)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15m-2(3+5m)= equation:


Simplifying
15m + -2(3 + 5m) = 0
15m + (3 * -2 + 5m * -2) = 0
15m + (-6 + -10m) = 0

Reorder the terms:
-6 + 15m + -10m = 0

Combine like terms: 15m + -10m = 5m
-6 + 5m = 0

Solving
-6 + 5m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 5m = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 5m = 0 + 6
5m = 0 + 6

Combine like terms: 0 + 6 = 6
5m = 6

Divide each side by '5'.
m = 1.2

Simplifying
m = 1.2

See similar equations:

| 15x^2-50y+35=0 | | 2-(8p-q)-7(p+6)+4q= | | -8x+x^2=-12 | | x^2-x-20=0 | | 7(p+3)=7b-4 | | f(11)=1/2(11)+5 | | 9(s+7)-(7s+m)-9m= | | f(11)=2(11)+5 | | 9(7x+8)+3(x+-10)= | | 7x+9=-11x+12 | | 7x+9and=-11x+12 | | -(9q+7)+3(2q-5)= | | 8y-2=14y-3 | | 20-4(w+1)=9w-4(9+w) | | 3(s-5)-7(4s-7)= | | 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 | | 2x+4x-8=34 | | 8y+10=16-8y | | 10x-7=3x+5 | | 15-5(3-8y)= | | -7(1+5x)+3=-8(4x+5) | | y=6sin(6x) | | 9(a-3)+2= | | 3.5x-20=2.4x-13 | | -x-x^2=14 |

Equations solver categories